PENGARUH PERSONALISASI LAYANAN, KOMUNIKASI AKTIF DAN CITRA SOSIAL DIGITAL TERHADAP KEPUASAN PELANGGAN GLEAMINGSHOESS SURABAYA - Kafiyanto, Umarul; Sigit Santoso (STAI Denpasar Bali, 2025)
This study aims to analyze the effect of service personalization, active communication, and digital social image on customer satisfaction at GleamingShoess, a shoe cleaning service business in Surabaya. The study used a quantitative method with a survey approach, where data was collected through questionnaires to GleamingShoess customers. Data analysis was carried out using multiple linear regression to test the effect of each independent variable on customer satisfaction with a sample of 100 respondents and using SPSS 26. The results showed that Service Personalization (X1) had a positive and significant effect on GleamingShoess customer satisfaction (Y), Active Communication (X2) had a negative and insignificant effect on GleamingShoess customer satisfaction (Y) and Digital Social Image (X3) had a positive and significant effect on GleamingShoess customer satisfaction (Y). This indicates that a service strategy that focuses on individual needs, responsive interactions, and a strong brand image on social media can increase customer satisfaction. This study provides practical implications for service business actors, especially in building customer loyalty through a digital approach and more personal communication. Keywords: service personalization, active communication, digital social image, customer satisfaction, GleamingShoess.